Method for preparing lithium titanate by recycling lithium titanate pole pieces, lithium titanate and application of lithium titanate
Through the calcination-acid leaching-decompression-depositing process, combined with the wet premix-drying-calcining process, the problem of complex and high pollution of lithium titanate waste electrode sheet recycling process has been successfully solved, and efficient lithium titanate recycling and reuse has been achieved.
Patent Information
- Application Number
- CN202411891770.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-25
AI Technical Summary
In the prior art, the process of recycling lithium titanate waste electrode sheets is complex and has high pollution, making it difficult to effectively solve this problem.
Lithium titanium dioxide was obtained by calcining the waste electrode sheet-acid leaching-decompression-depositing lithium, and lithium carbonate was obtained by calcining the acid leaching filter cake, and titanium dioxide was obtained, and then lithium titanium was prepared by a wet premixing-drying-calcining monosurgery process.
It realizes efficient decomposition and recycling of lithium titanate in waste electrode sheets, reduces impurities content, avoids pollution caused by mechanical crushing, and is simple and easy to perform, and is suitable for mass production.
Smart Images

Figure CN119873882A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery material recycling, and in particular to a method for recycling lithium titanate pole pieces to prepare lithium titanate, lithium titanate and applications thereof. Background Art
[0002] The volume change of lithium titanate material during the charge and discharge process of lithium ion insertion and removal is very small, almost zero, and it is called "zero strain" material. In addition, it has a very stable 1.5V (vs.Li) discharge platform, which is higher than the reduction potential of most electrolyte solvents. Therefore, compared with other negative electrode materials, lithium titanate material does not form SEI film and has high coulomb efficiency. Due to its zero strain characteristics, lithium titanate material has high safety. At present, lithium titanate batteries have been widely used in new energy batteries, electric motorcycles, auxiliary power grid energy storage systems and other fields. However, in the production process of lithium titanate battery materials, unqualified products with low energy density and low gram capacity will inevitably be produced, which cannot be applied to lithium titanate batteries, nor can they meet the material requirements of lithium titanate batteries. It is necessary to recycle the valuable elements in the waste lithium titanate pole pieces.
[0003] Patent application number 201810496708.9 provides a method for preparing lithium titanate negative electrode materials. Hydrogen peroxide and the like are used as reducing agents during lithium titanate recovery. A titanium complex is obtained after acid leaching. Subsequently, titanium and lithium elements are separated by extraction. However, this method has the disadvantages of complex extraction process and high pollution. In addition, lithium battery recovery technology is mainly related to lithium iron phosphate and ternary lithium batteries, while research on the recovery of lithium titanate is still relatively rare. Summary of the invention
[0004] The main purpose of the present invention is to provide a method for recycling lithium titanate pole pieces to prepare lithium titanate, lithium titanate and its application, so as to solve the problems of complex process and high pollution in the prior art of recycling waste lithium titanate pole pieces.
[0005] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, there is provided a method for recovering lithium titanate pole pieces to prepare lithium titanate, comprising the following steps: step S1, subjecting the lithium titanate pole pieces to a first calcination to obtain a first calcination product; step S2, subjecting the first calcination product to acid leaching, filtering, and obtaining an acid leaching filtrate and an acid leaching filter cake; step S3, adjusting the pH of the acid leaching filtrate to 10-12 to remove impurities and obtain an impurity-removing solution; step S4, adding carbonate to the impurity-removing solution to precipitate lithium to obtain lithium carbonate; step S5, subjecting the acid leaching filter cake to a second calcination to obtain titanium dioxide; step S6, mixing lithium carbonate, titanium dioxide, an optional lithium source, an optional titanium source, a dispersant, and a solvent to obtain a mixed solution; step S7, sequentially drying and third calcining the mixed solution to obtain remade lithium titanate; wherein, an acid solution having a molar concentration of 2-6M is used for acid leaching, and the acid solution comprises one or more of sulfuric acid, hydrochloric acid, and nitric acid.
[0006] Furthermore, in step S1, the lithium titanate pole piece includes waste lithium titanate, a conductive agent and a binder, and the weight ratio of the waste lithium titanate, the conductive agent and the binder is (86-94):(3-7):(3-7); and / or, the temperature of the first calcination is 400-500°C, and the time is 2-4h.
[0007] Furthermore, in step S2, the acid leaching temperature is 90-100° C., and the time is 2-4 h; and / or the molar ratio of the first calcined product to the acid in the acid solution is 1:(1-1.4).
[0008] Further, in step S3, the impurity removal step includes: first adjusting the pH of the acid leaching filtrate to 6-8, performing a first filtration to obtain an intermediate impurity removal solution, continuing to adjust the pH of the intermediate impurity removal solution to 10-12, and performing a second filtration to obtain an impurity removal solution; and / or, the impurity removal temperature is 40-60°C; and / or, one or more of sodium hydroxide solution, potassium hydroxide solution and ammonia solution are used for impurity removal; and / or, in step S4, the weight ratio of carbonate to impurity removal solution is 1:(6-8); and / or, the carbonate includes one or more of sodium carbonate, potassium carbonate and ammonium carbonate; and / or, the temperature of lithium precipitation is 80-100°C, and the time is 0.5-2h.
[0009] Furthermore, in step S5, the temperature of the second calcination is 400-600° C., and the time is 1-4 hours.
[0010] Further, in step S6, in step S6, the ratio of the sum of the weights of lithium carbonate and titanium dioxide to the sum of the weights of the lithium source and the titanium source is (0.5-3):(7-9.5); and / or, the solid content of the mixed solution is 15-25%; and / or, in the mixed solution, the molar ratio of lithium to titanium is (0.78-0.84):1; and / or, in step S7, the drying is spray drying, the inlet temperature of the spray drying is 220-360°C, and the outlet temperature is 85-115°C; and / or, the gas flow rate during the drying process is 5-7m 3 / h; and / or, the temperature of the third calcination is 600-900°C and the time is 2-8h.
[0011] Furthermore, the recovery rate of waste lithium titanate is ≥85%; and / or the purity of the reset lithium titanate is ≥99%; and / or the particle size D10 of the remade lithium titanate is 2.0-4.3 μm, D50 is 7.0-11.0 μm, D90 is 16-26.2 μm, and D99 is 30.0-40.0 μm; and / or the gram capacity of the remade lithium titanate is ≥160 mAh / g, and the first efficiency is ≥98%.
[0012] According to another aspect of the present invention, there is provided a lithium titanate prepared according to the above method.
[0013] According to another aspect of the present invention, there is provided an electrode comprising the above-mentioned lithium titanate.
[0014] According to another aspect of the present invention, a lithium battery is provided, comprising the above-mentioned electrode.
[0015] In the method for recovering lithium titanate pole pieces and preparing lithium titanate of the present invention, lithium carbonate is obtained by calcining-acid leaching-impurity removal-lithium precipitation of waste pole pieces, and titanium dioxide is obtained by calcining the acid leaching filter cake at the same time, and lithium titanate is obtained by secondary preparation through a wet premixing-drying-calcining one-burning process, so as to achieve the decomposition and recycling of lithium titanate in waste lithium titanate pole pieces. The method of the present invention can not only recover the lithium titanate elements in the waste pole pieces, but also reuse the titanium and lithium elements in the lithium titanate. In addition, the method of the present invention does not use mechanical crushing, which effectively reduces the impurity content in the lithium titanate, and uses dilute acid instead of hydrogen peroxide and concentrated sulfuric acid for acid leaching, which avoids the harm of reagents to the human body during the operation process, and has the advantages of simple and easy process, relatively less pollution, and can be implemented in mass production.
[0016] The method has a high recovery rate of lithium titanate in lithium titanate pole pieces, and the prepared lithium titanate has low cost and high purity, and the capacity and charge-discharge performance are comparable to those of normally produced lithium titanate, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0018] Figure 1 A schematic diagram of the process of recycling lithium titanate pole pieces to prepare lithium titanate according to Example 1 of the present invention is shown;
[0019] Figure 2 shows a SEM morphology of the remade lithium titanate according to Example 1 of the present invention; and
[0020] Figure 3 The XRD morphology diagrams of lithium titanate according to Example 1 and Comparative Example 1 of the present invention are shown. DETAILED DESCRIPTION
[0021] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0022] As described in the background of the present invention, the prior art has the problems of complex process and high pollution in recycling waste lithium titanate pole pieces. In order to solve the above problems, in a typical embodiment of the present invention, a method for recovering lithium titanate pole pieces to prepare lithium titanate is provided, comprising the following steps: step S1, performing a first calcination on the lithium titanate pole piece to obtain a first calcination product; step S2, acid leaching the first calcination product, filtering, and obtaining an acid leaching filtrate and an acid leaching filter cake; step S3, adjusting the pH of the acid leaching filtrate to 10-12 to remove impurities and obtain an impurity removal solution; step S4, adding sodium carbonate to the impurity removal solution to precipitate lithium to obtain lithium carbonate; step S5, performing a second calcination on the acid leaching filter cake to obtain titanium dioxide; step S6, mixing lithium carbonate, titanium dioxide with a lithium source, a titanium source, a dispersant, and a solvent to obtain a mixed solution; step S7, drying and third calcining the mixed solution in sequence to obtain remade lithium titanate; wherein, an acid solution with a molar concentration of 2-6M is used for acid leaching, and the acid solution includes one or more of sulfuric acid, hydrochloric acid, and nitric acid.
[0023] In the prior art, mechanical crushing is usually used to process waste pole pieces. However, the inventors of the present application have taken into special consideration that mechanical crushing will cause residual debris in the aluminum foil in the pole piece, making the subsequent impurity removal process complicated. Based on this, the present application particularly uses calcination to process the pole piece, which can not only effectively prevent a large amount of impurities caused by the crushing of the pole piece aluminum foil from entering the subsequent process, thereby effectively reducing the impurity content in the lithium titanate product, but also effectively make the lithium titanate on the lithium titanate pole piece fall off, effectively improving the recovery rate of lithium titanate on the pole piece.
[0024] In addition, in the prior art, hydrogen peroxide and concentrated sulfuric acid are usually used to acid-leach lithium titanate-containing materials to extract the beneficial elements therein. The inventors of this application have taken into account that when hydrogen peroxide and concentrated sulfuric acid are used, the reaction is not easy to control, and the impurity removal process requires an extraction process, which has a long process flow and complicated operation. In addition, in actual operation, the safety risk of human body burns caused by improper handling of concentrated sulfuric acid is high. Therefore, this application specifically uses a molar concentration of 2 to 6M, one or more of sulfuric acid, hydrochloric acid and nitric acid for acid leaching, which can not only effectively reduce safety risks, but also has a simple process, relatively less pollution, and is easy to implement, and can be mass-produced.
[0025] In the method of the present application, the lithium titanate pole piece is first calcined. During this process, the conductive agent, binder and other components in the pole piece are mainly lost in the form of carbon dioxide and water, and the main component of the obtained lithium titanate-containing material is lithium titanate; then, acid leaching is carried out using a dilute acid solution. During this process, the following reaction occurs: Li4Ti5O 12 +2H2SO4+8H2O=2Li2SO4+5H4TiO4, Li2SO4 enters the acid leaching filtrate, and H4TiO4 enters the acid leaching filter cake. It should be noted that the present application specifically limits the acid solution used in the acid leaching process to one or more of sulfuric acid, hydrochloric acid and nitric acid with a molar concentration of 2 to 6M. The inventors found that under the above conditions, the chemical reaction rate is fast, and titanium and lithium elements can be fully dissolved and recovered.
[0026] Then, the acid leaching filtrate is decontaminated and the pH end point is adjusted to 10-12 to remove impurity ions (such as aluminum ions, etc.); secondly, carbonate is added to the decontaminated solution to precipitate lithium to obtain lithium carbonate. In addition, the acid leaching filter cake is calcined, and during this process, H4TiO4 is converted into titanium dioxide. The obtained lithium carbonate and titanium dioxide are wet premixed with an optional lithium source, an optional titanium source, a dispersant, and a solvent to obtain a mixed solution, and then dried and calcined to prepare lithium titanate.
[0027] In summary, in the method of recycling lithium titanate pole pieces to prepare lithium titanate in the present application, lithium carbonate is obtained by calcining the waste pole pieces, acid leaching, impurity removal, and lithium precipitation. At the same time, titanium dioxide is obtained by calcining the acid leaching filter cake, and lithium titanate is obtained by secondary preparation through a wet premixing-drying-calcining one-burning process, so as to achieve the decomposition and recycling of lithium titanate in waste lithium titanate pole pieces. The method of the present application can not only recover the elements of lithium titanate in waste pole pieces, but also reuse the titanium and lithium elements in lithium titanate. Moreover, the method of the present application does not use mechanical crushing, which can effectively reduce the impurity content in lithium titanate, and uses a dilute acid with a molar concentration of 2 to 6M instead of hydrogen peroxide and concentrated sulfuric acid for acid leaching, which can avoid the harm of reagents to the human body during the operation process, and has the advantages of simple process, easy operation, relatively less pollution, and mass production. The present method has a high recovery rate of lithium titanate in lithium titanate pole pieces and a low cost for preparing lithium titanate.
[0028] The method of the present application is applicable to the treatment of conventional lithium titanate pole pieces. In a preferred embodiment, in step S1, the lithium titanate pole piece includes waste lithium titanate, a conductive agent and a binder, and the weight ratio of the three is (86-94): (3-7): (3-7); and / or, the temperature of the first calcination is 400-500°C, and the time is 2-4 hours. Under this condition, the lithium titanate component in the waste pole piece can be extracted more effectively, and fewer impurities enter the subsequent process, which is more conducive to improving the purity of the lithium titanate product.
[0029] In order to further improve the recovery rate and recovery efficiency of titanium and lithium elements, in a preferred embodiment, in step S2, the acid leaching temperature is 90-100°C and the time is 2-4 hours; and / or the molar ratio of the first calcined product to the acid in the acid solution is 1:(1-1.4).
[0030] In a preferred embodiment, in step S3, the impurity removal step includes: first adjusting the pH of the acid leaching filtrate to 6-8, performing a first filtration to obtain an intermediate impurity removal solution, continuing to adjust the pH of the intermediate impurity removal solution to 10-12, and performing a second filtration to obtain an impurity removal solution. In the present application, the pH of the acid leaching filtrate is first adjusted to 6-8, which can more effectively remove aluminum ions and iron ions in the solution, and then adjusting the pH to 10-12 can further remove metal ions such as divalent iron ions and manganese ions, thereby more effectively removing impurities, improving the recovery efficiency and purity of lithium ions, and further reducing the difficulty and cost of subsequent processing steps.
[0031] In order to more fully remove impurities, to further improve the purity of the lithium titanate product, and to further improve the rate of impurity removal, in a preferred embodiment, the impurity removal temperature is 40-60°C; and / or, one or more of sodium hydroxide solution, potassium hydroxide solution and ammonia solution are used for impurity removal; and / or, in step S4, the weight ratio of carbonate to impurity removal solution is 1:(6-8); and / or, the carbonate includes one or more of sodium carbonate, potassium carbonate and ammonium carbonate.
[0032] In a preferred embodiment, the temperature of lithium precipitation is 80-100° C. and the time is 0.5-2 hours. Under the above conditions, it is more conducive to the lithium precipitation reaction, and the purity and yield of the obtained lithium carbonate are higher.
[0033] In a preferred embodiment, in step S5, the temperature of the second calcination is 400-600°C and the time is 1-4 hours; and / or, step S5 also includes the step of washing the acid leaching filter cake. Under the above conditions, the H4TiO4 in the acid leaching filter cake can be more fully converted into titanium dioxide. If the temperature is too high or the time is too long, it will lead to increased energy consumption. If the temperature is too low or the time is too short, it is easy to cause incomplete reaction, resulting in lower purity of titanium dioxide, further affecting the purity of the product lithium titanate.
[0034] In order to further improve the utilization rate of the above-mentioned lithium carbonate and titanium dioxide, and at the same time make them more fully coordinated with the lithium source, titanium source, solvent and dispersant to further improve the performance of lithium titanate products, in a preferred embodiment, in step S6, the ratio of the sum of the weight of lithium carbonate and titanium dioxide to the sum of the weight of the lithium source and the titanium source is (0.5-3):(7-9.5); and / or, the lithium source includes one or more of lithium salts, lithium oxide and lithium hydroxide; and / or, the titanium source includes one or more of titanium dioxide, titanium hydroxide, metatitanic acid and TiO(OH)2; and / or, the dispersant includes one or more of anhydrous ethanol, ethylene glycol and polyethylene glycol; and / or, the solvent includes water; and / or, the solid content of the mixed solution is 15-25%; and / or, in the mixed solution, the molar ratio of lithium to titanium is (0.78-0.84):1.
[0035] In a preferred embodiment, in step S7, the drying is spray drying, the inlet temperature of the spray drying is 220-360°C, and the outlet temperature is 85-115°C; and / or the gas flow rate during the drying process is 5-7m / s. 3 / h. Under the above conditions, it is more conducive to forming spherical precursors of various materials, which is more conducive to improving the gram capacity and energy density of the product lithium titanate.
[0036] In order to further improve the quality and performance of lithium titanate products, in a preferred embodiment, the temperature of the third calcination is 600-900°C and the time is 2-8 hours. If the calcination temperature is too high or the time is too long, it may cause excessive grain growth, increase in side reactions or structural damage, thereby reducing the energy density and gram capacity of lithium titanate. If the temperature is too low or the time is too short, it may affect the degree of reaction and easily lead to incomplete reaction, which will also affect the purity and gram capacity of lithium titanate.
[0037] In order to make the lithium titanate product more convenient for practical use, in a preferred embodiment, step S7 also includes a step of screening the lithium titanate.
[0038] In a preferred embodiment, the recovery rate of waste lithium titanate is ≥85%; and / or the purity of the remade lithium titanate is ≥99%; and / or the particle size D10 of the remade lithium titanate is 2.0-4.3 μm, D50 is 7.0-11.0 μm, D90 is 16-26.2 μm, and D99 is 30.0-40.0 μm; and / or the gram capacity of the remade lithium titanate is ≥160 mAh / g, and the first efficiency is ≥98%.
[0039] In another typical embodiment of the present invention, a lithium titanate is also provided, which is prepared according to the above method. Among the raw materials of the lithium titanate product of the present application, part of the titanium source and lithium source are derived from waste lithium titanate pole pieces, so that the titanium and lithium elements of the waste lithium titanate pole pieces are fully recycled, and the lithium titanate product has low cost, high purity, and the capacity and charge-discharge performance are comparable to those of normally produced lithium titanate, and has broad application prospects.
[0040] In another typical embodiment of the present invention, an electrode is also provided, comprising the above-mentioned lithium titanate. The raw materials of lithium titanate in the electrode of the present application, part of the titanium source and lithium source are derived from waste lithium titanate pole pieces, so that the titanium element and lithium element of the waste lithium titanate pole pieces are fully recycled, and the cost of the electrode is low, and the capacity and charge-discharge performance are comparable to those of normally produced electrodes, and it has a wide range of application prospects.
[0041] In another typical embodiment of the present invention, a lithium battery is provided, comprising the above-mentioned electrode. The raw materials of the lithium titanate product in the battery of the present application, part of the titanium source and lithium source are derived from the waste lithium titanate pole pieces, so that the titanium and lithium elements of the waste lithium titanate pole pieces are fully recycled, and the cost of the electrode is low, and the capacity and charge-discharge performance are comparable to those of normally produced batteries, and it has a wide range of application prospects.
[0042] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0043] Example 1
[0044] The schematic diagram of the process of recycling lithium titanate pole pieces to prepare lithium titanate is shown in Figure 1 .
[0045] Step S1, placing the waste lithium titanate pole piece (wherein the ratio of lithium titanate, conductive carbon black and binder PVDF is 90:5:5) in a muffle furnace, calcining at 400° C. for 2 hours, and performing ultrasound after cooling to obtain a powder containing lithium titanate.
[0046] Step S2, adding the powder into a dilute sulfuric acid solution with a molar concentration of 4M, with the molar ratio of the first calcined product to the sulfuric acid being 1:1.2, stirring with a magnetic bar at 95°C for 2h, and performing filter pressing to obtain an acid leaching filtrate and an acid leaching filter cake.
[0047] Step S3, adding sodium hydroxide to the acid leaching filtrate to pH=7, stirring for 30 minutes, and filtering by pressure to obtain an intermediate impurity removal filtrate and aluminum hydroxide residue. Sodium hydroxide is continued to be added to the intermediate impurity removal filtrate to adjust the pH to 11, and then stirred at 50°C for 30 minutes, and filtered by pressure to obtain an impurity removal solution and a residue (mainly aluminum hydroxide).
[0048] Step S4, then add sodium carbonate to the impurity removal solution (the weight ratio of sodium carbonate to the impurity removal solution is 1:7), stir at a temperature of 90° C. for 1 hour, and obtain lithium carbonate by centrifugal separation, filtration, and washing.
[0049] Step S5, taking the acid leaching filter cake in step 1, washing it with water three times, and then placing it in a muffle furnace and calcining it at 600° C. for 4 hours to obtain titanium dioxide.
[0050] Step S6, mixing the above-mentioned lithium carbonate, the above-mentioned titanium dioxide with a lithium source (LiOH·H2O), a titanium source (metatitanic acid), water, and a dispersant (ethanol) to obtain a mixed solution, wherein the ratio of the sum of the weights of the lithium carbonate and the titanium dioxide to the sum of the weights of the lithium source and the titanium source is 1:9, the molar ratio of lithium to titanium is 0.81:1, and the solid content of the mixed solution is 20%; then, the mixed solution is ball-milled (the ball mill is filled with 0.2mm zirconium balls, and the effective power of the ball milling is 0.5kwh).
[0051] Step S7, the mixed solution is then transferred to a spray drying tower, the inlet air temperature of the spray drying tower is 250°C, the outlet air temperature is 100°C, and the gas flow rate during the drying process is 6m 3 / h. Subsequently, the spray-dried material was filled into an alumina crucible, and then placed into a muffle furnace for calcination in an air atmosphere at a temperature of 750°C for 4 hours. Finally, the sintered product was sieved with a 200-mesh sieve to obtain the re-synthesized lithium titanate. The SEM morphology of the re-synthesized lithium titanate is shown in Figure 2 .
[0052] The remade lithium titanate, superconducting carbon black and binder were mixed and stirred evenly to form a negative electrode plate, which was then combined with a metal lithium positive electrode plate and 1M LiPF6-EC / DMC (volume ratio of 1:1) electrolyte to form a lithium-ion battery, and the button cell was assembled in an argon-filled glove box for measurement.
[0053] Example 2
[0054] The schematic diagram of the process of recycling lithium titanate pole pieces to prepare lithium titanate is shown in Figure 1 .
[0055] Step S1, placing the waste lithium titanate pole piece (wherein the ratio of lithium titanate, conductive carbon black and binder PVDF is 90:5:5) in a muffle furnace, calcining at 450° C. for 2.5 hours, and performing ultrasound after cooling to obtain a powder containing lithium titanate.
[0056] Step S2, adding the powder into a dilute sulfuric acid solution with a molar concentration of 2M, wherein the molar ratio of the first calcined product to the sulfuric acid is 1:1.2, stirring with a magnetic stirrer at 95°C for 3 hours, and performing filter pressing to obtain an acid leaching filtrate and an acid leaching filter cake.
[0057] Step S3, adding sodium hydroxide to the acid leaching filtrate to pH=7, stirring for 40 minutes, and filtering by pressure to obtain an intermediate impurity removal filtrate and aluminum hydroxide filter residue. Sodium hydroxide is continued to be added to the intermediate impurity removal filtrate to adjust the pH to 11, and then stirred at 50°C for 40 minutes, and filtered by pressure to obtain an impurity removal solution and filter residue.
[0058] Step S4, then add sodium carbonate to the impurity removal solution (the weight ratio of sodium carbonate to the impurity removal solution is 1:7), stir at a temperature of 90° C. for 1.5 hours, and obtain lithium carbonate by centrifugal separation, filtration, and washing.
[0059] Step S5, taking the acid leaching filter cake in step 1, washing it with water three times, and then placing it in a muffle furnace and calcining it at 500° C. for 2 hours to obtain titanium dioxide.
[0060] Step S6, mixing the above-mentioned lithium carbonate, the above-mentioned titanium dioxide with a lithium source (LiOH·H2O), a titanium source (metatitanic acid), water, and a dispersant (ethanol) to obtain a mixed solution, wherein the ratio of the sum of the weights of lithium carbonate and titanium dioxide to the sum of the weights of the lithium source and the titanium source is 1.5:8.5, the molar ratio of lithium to titanium is 0.81:1, and the solid content of the mixed solution is 20%; then, the mixed solution is ball-milled (the ball mill is filled with 0.4mm zirconium balls, and the effective power of the ball milling is 3kwh).
[0061] Step S7, the mixed solution is then transferred to a spray drying tower, the inlet air temperature of the spray drying tower is 250°C, the outlet air temperature is 115°C, and the gas flow rate during the drying process is 6m 3 / h. Subsequently, the spray-dried material was filled into an alumina crucible, and then placed into a muffle furnace for calcination in an air atmosphere at a temperature of 750°C for 4 hours. Finally, the sintered product was sieved with a 200-mesh sieve to obtain the re-synthesized lithium titanate.
[0062] Example 3
[0063] The only difference from Example 1 is:
[0064] Step S1, placing the waste lithium titanate pole piece (wherein the ratio of lithium titanate, conductive carbon black and binder PVDF is 86:7:7) in a muffle furnace, calcining at 400° C. for 4 hours, and performing ultrasound after cooling to obtain a powder containing lithium titanate.
[0065] Step S2, adding the powder into a dilute sulfuric acid solution with a molar concentration of 6M, with the molar ratio of the first calcined product to the acid solution being 1:1.1, stirring with a magnetic stirrer at 90°C for 4 hours, and performing filter pressing to obtain an acid leaching filtrate and an acid leaching filter cake.
[0066] Step S3, adding an ammonia solution to the acid leaching filtrate to a pH of 8, stirring for 40 minutes, and filtering by pressure to obtain an intermediate impurity removal filtrate and an aluminum hydroxide filter residue. Continue to add an ammonia solution to the intermediate impurity removal filtrate to adjust the pH to 10, then stir at 40° C. for 40 minutes, and filter by pressure to obtain an impurity removal solution and a filter residue.
[0067] Step S4, then add sodium carbonate to the impurity removal solution (the weight ratio of sodium carbonate to the impurity removal solution is 1:6), stir at a temperature of 100° C. for 0.5 h, and obtain lithium carbonate by centrifugal separation, filtering and washing.
[0068] Example 4
[0069] The only difference from Example 1 is:
[0070] The schematic diagram of the process of recycling lithium titanate pole pieces to prepare lithium titanate is shown in Figure 1 .
[0071] Step S1, placing the waste lithium titanate pole piece (wherein the ratio of lithium titanate, conductive carbon black and binder PVDF is 94:3:3) in a muffle furnace, calcining at 500° C. for 2 hours, and performing ultrasound after cooling to obtain a powder containing lithium titanate.
[0072] Step S2, adding the powder into a dilute sulfuric acid solution with a molar concentration of 2M, with the molar ratio of the first calcined product to the acid solution being 1:1.4, stirring with a magnetic bar at 100°C for 2h, and performing filter pressing to obtain an acid leaching filtrate and an acid leaching filter cake.
[0073] Step S3, adding potassium hydroxide solution to the acid leaching filtrate to pH=6, stirring for 40 minutes, and filtering by pressure to obtain an intermediate impurity removal filtrate and aluminum hydroxide filter residue. Continue to add potassium hydroxide solution to the intermediate impurity removal filtrate to adjust the pH to 12, then stir at 60°C for 40 minutes, and filter by pressure to obtain an impurity removal solution and filter residue.
[0074] Step S4, then add ammonium carbonate to the impurity removal solution (the weight ratio of ammonium carbonate to the impurity removal solution is 1:8), stir at a temperature of 80° C. for 2 hours, and obtain lithium carbonate by centrifugal separation, filtration, and washing.
[0075] Example 5
[0076] The only difference from Example 1 is:
[0077] Step S5, taking the acid leaching filter cake in step 1, washing it with water three times, and then placing it in a muffle furnace and calcining it at 400° C. for 6 hours to obtain titanium dioxide.
[0078] Example 6
[0079] The only difference from Example 1 is:
[0080] Step S5, taking the acid leaching filter cake in step 1, washing it with water three times, and then placing it in a muffle furnace and calcining it at 600° C. for 1 hour to obtain titanium dioxide.
[0081] Example 7
[0082] The only difference from Example 1 is:
[0083] Step S6, mixing the lithium carbonate in step S4 of Example 1 and the titanium dioxide in step S5 of Example 1 with a lithium source (LiOH·H2O), a titanium source (metatitanic acid), water, and a dispersant (ethanol) to obtain a mixed solution, wherein the ratio of the sum of the weights of the lithium carbonate and the titanium dioxide to the sum of the weights of the lithium source and the titanium source is 1:7, the molar ratio of lithium to titanium is 0.84:1, and the solid content of the mixed solution is 15%; then, the mixed solution is ball-milled (the ball mill is filled with 0.2 mm zirconium balls, and the effective power of the ball milling is 0.5 kwh).
[0084] Step S7, the mixed solution is then transferred to a spray drying tower, the inlet air temperature of the spray drying tower is 220°C, the outlet air temperature is 85°C, and the gas flow rate during the drying process is 7m 3 / h. Subsequently, the spray-dried material was filled into an alumina crucible, and then placed into a muffle furnace for calcination in an air atmosphere at a temperature of 600°C for 8 hours. Finally, the sintered product was sieved with a 200-mesh sieve to obtain the re-synthesized lithium titanate.
[0085] Example 8
[0086] The only difference from Example 1 is:
[0087] Step S6, mixing the lithium carbonate, the titanium dioxide, a lithium source (LiOH·H2O), a titanium source (metatitanic acid), water, and a dispersant (ethanol) to obtain a mixed solution, wherein the ratio of the sum of the weights of the lithium carbonate and the titanium dioxide to the sum of the weights of the lithium source and the titanium source is 1:9.5, the solid content of the mixed solution is 25%, and the molar ratio of lithium to titanium is 0.78:1; then, the mixed solution is ball-milled (the ball mill is filled with 0.2 mm zirconium balls, and the effective power of the ball milling is 0.5 kwh).
[0088] Step S7, the mixed solution is then transferred to a spray drying tower, the inlet air temperature of the spray drying tower is 360°C, the outlet air temperature is 115°C, and the gas flow rate during the drying process is 6m 3 / h. Subsequently, the spray-dried material was filled into an alumina crucible, and then placed into a muffle furnace for calcination in an air atmosphere at a temperature of 900°C for 2 hours. Finally, the sintered product was sieved with a 200-mesh sieve to obtain the re-synthesized lithium titanate.
[0089] Comparative Example 1
[0090] A method for preparing lithium titanate comprises the following steps:
[0091] Step S1, mixing a lithium source (lithium oxide), a titanium source (titanium dioxide), water, and a dispersant (anhydrous ethanol) to obtain a mixed solution, wherein the molar ratio of the titanium element in the titanium source to the lithium element in the lithium source can be 1:0.84, the weight percentage of the solvent in the mixed solution is 20%, and the weight percentage of the dispersant in the mixed solution is 2%. Then, the mixed solution is ball-milled (the ball mill is filled with 0.2mm zirconium balls, and the effective power of the ball milling is 0.5kwh).
[0092] Step S2, then transfer to a spray drying tower, the inlet air temperature of the spray drying tower is 250°C, the outlet air temperature is 100°C, and the gas flow rate during the drying process is 6m 3 / h. Subsequently, the spray-dried material was filled into an alumina crucible, and then placed into a muffle furnace for calcination in an air atmosphere at a temperature of 750°C for 4 hours. Finally, the sintered product was sieved with a 200-mesh sieve to obtain lithium titanate produced under normal conditions as a comparative sample, and the lithium titanate prepared by recycling the lithium titanate pole piece in Example 1 was used as a control to evaluate the characteristics and performance of the remade lithium titanate in Example 1.
[0093] The XRD pattern of lithium titanate is shown in Figure 3After analysis, it can be seen that according to the spectrum, the peak completely corresponds to the standard spectrum of lithium titanate (LTO) (PDFNO.49-0207). According to the data conversion, the phase purity is 100.00%, and the peak shape is sharp, and the crystallinity of the material is good.
[0094] Comparative Example 2
[0095] Chinese patent embodiment 1 with application number 201810496708.9.
[0096] Comparative Example 3
[0097] Chinese patent embodiment 1 with application number 201510372381.0.
[0098] The characteristic parameter results of lithium titanate prepared in the above examples and comparative examples are shown in Table 1, and the performance test results are shown in Table 2 and Table 3.
[0099] Test method:
[0100] Particle size distribution: measured by laser particle size analyzer. The sample is directly added into water for dispersion, and then passes through the optical path system to calculate the particle size distribution.
[0101] Specific surface area: measured by BET method.
[0102] XRD determination of phase purity: MiniFlex 600 X-ray diffractometer was used for testing. The scanning angle range was 10-80° and the scanning rate was 3° / min.
[0103] Gram capacity and charge-discharge capacity retention rate: tested using the Xinwei battery testing system (CT-4008-5V10mA-164).
[0104] Table 1
[0105]
[0106] Table 2
[0107]
[0108]
[0109] Table 3
[0110]
[0111] As can be seen from the above, in the method of recycling lithium titanate pole pieces to prepare lithium titanate in the present application, lithium carbonate is obtained by calcining-acid leaching-impurity removal-lithium precipitation of waste pole pieces, and titanium dioxide is obtained by calcining the acid leaching filter cake at the same time, and lithium titanate is obtained by secondary preparation through a wet premixing-drying-calcining one-burning process, so as to achieve the decomposition and recycling of lithium titanate in waste lithium titanate pole pieces. The method of the present application can not only recover the lithium titanate elements in the waste pole pieces, but also reuse the titanium and lithium elements in the lithium titanate. Moreover, the method of the present application does not use mechanical crushing, which effectively reduces the impurity content in the lithium titanate, and uses dilute sulfuric acid instead of hydrogen peroxide and concentrated sulfuric acid for acid leaching, which avoids the harm of reagents to the human body during the operation, and has the advantages of simple and easy process, relatively less pollution, and can be implemented in mass production.
[0112] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for recycling lithium titanate pole pieces to prepare lithium titanate, characterized in that: The following steps are involved: Step S1, performing a first calcination on the lithium titanate pole piece to obtain a first calcined product; Step S2, acid leaching the first calcined product, filtering it, and obtaining an acid leaching filtrate and an acid leaching filter cake; Step S3, adjusting the pH of the acid leaching filtrate to 10-12 to remove impurities and obtain an impurity-removing solution; Step S4, adding carbonate to the impurity removal solution to precipitate lithium to obtain lithium carbonate; Step S5, performing a second calcination on the acid leaching filter cake to obtain titanium dioxide; Step S6, mixing the lithium carbonate, the titanium dioxide, an optional lithium source, an optional titanium source, a dispersant, and a solvent to obtain a mixed solution; Step S7, sequentially drying and third calcining the mixed solution to obtain remade lithium titanate; Wherein, the acid leaching is carried out using an acid solution with a molar concentration of 2 to 6 M, and the acid solution includes one or more of sulfuric acid, hydrochloric acid and nitric acid.
2. The method according to claim 1, characterized in that In the step S1, The lithium titanate pole piece includes waste lithium titanate, a conductive agent and a binder, and the weight ratio of the three is (86-94): (3~7):(3~7); and / or, The first calcination is carried out at a temperature of 400 to 500° C. and for a time of 2 to 4 hours.
3. The method according to claim 1 or 2, characterized in that: In the step S2, The acid leaching temperature is 90-100°C and the time is 2-4 hours; and / or, The molar ratio of the first calcined product to the acid in the acid solution is 1:(1-1.4).
4. The method according to any one of claims 1 to 3, characterized in that In the step S3, The impurity removal step comprises: first adjusting the pH of the acid leaching filtrate to 6-8, performing a first filtration to obtain an intermediate impurity removal solution, continuing to adjust the pH of the intermediate impurity removal solution to 10-12, and performing a second filtration to obtain the impurity removal solution; and / or, The impurity removal temperature is 40-60°C; and / or, The impurity removal is performed using one or more of sodium hydroxide solution, potassium hydroxide solution and ammonia solution; and / or, In the step S4, The weight ratio of the carbonate to the impurity removal solution is 1:(6-8); and / or, The carbonate includes one or more of sodium carbonate, potassium carbonate and ammonium carbonate; and / or, The temperature of the lithium deposition is 80-100° C. and the time is 0.5-2 hours.
5. The method according to any one of claims 1 to 4, characterized in that In the step S5, The second calcination temperature is 400-600° C. and the time is 1-4 hours.
6. The method according to any one of claims 1 to 5, characterized in that In step S6, The ratio of the sum of the weight of the lithium carbonate and the titanium dioxide to the sum of the weight of the lithium source and the titanium source is (0.5-3):(7-9.5); and / or, The solid content of the mixed solution is 15-25%; and / or, In the mixed solution, the molar ratio of lithium to titanium is (0.78-0.84):1; and / or, In step S7, The drying is spray drying, the inlet temperature of the spray drying is 220-360° C., and the outlet temperature is 85-115° C.; and / or, The gas flow rate during the drying process is 5 to 7 m 3 / h; and / or, The temperature of the third calcination is 600-900° C., and the time is 2-8 hours.
7. The method according to any one of claims 1 to 6, characterized in that The recovery rate of lithium titanate in the lithium titanate pole piece is ≥85%; and / or, The purity of the remade lithium titanate is ≥ 99%; and / or, The particle size D10 of the remade lithium titanate is 2.0-4.3 μm, D50 is 7.0-11.0 μm, D90 is 16-26.2 μm, and D99 is 30.0-40.0 μm; and / or, The gram capacity of the remade lithium titanate is ≥160 mAh / g, and the first efficiency is ≥98%.
8. A lithium titanate, characterized in that: Prepared according to the method according to any one of claims 1 to 7.
9. An electrode, characterized in that: Including the lithium titanate as described in claim 8.
10. A lithium battery, characterized in that: Comprising the electrode according to claim 9.
Citation Information
Patent Citations
Methods for recovering battery-grade iron phosphate from lithium iron phosphate batteries and for preparing lithium iron phosphate cathode materials from spent lithium iron phosphate batteries
CN104953200B
Preparation method and applications of lithium titanate negative electrode material
CN110510664A